O ser cientista brasileira em uma universidade portuguesa - Januário, Letícia Azevedo (2022)
The research emerges from the encounter of case reports involving discrimination and harassment directed at Brazilian women in Portuguese universities with my experiences as a university student in Portugal. The intentionality is to unveil the phenomenon “what is it to be a Brazilian scientist in a Portuguese university”. Therefore, the phenomenological interrogation guiding the research is “What is it to be a Brazilian woman in a Portuguese university?”. The theoretical foundations chosen to construct this research were the coloniality of power/being/knowledge, feminist theory, especially decolonial feminism, and gender studies in Social Studies of Science. The methodological procedures are inspired by phenomenology as a philosophical method, specifically in the approach of the Situated Phenomenon. Socializations were conducted with the research participants and registered in a field diary, followed by interviews with the intention of giving voice to those who experience the phenomenon to be unveiled. The profile of the participants is composed of Brazilian women in academic activity in Portuguese universities at the postgraduate level, and exclusion criteria were not adopted. Altogether, ten interviews were carried out, transcribed, and analysed according to the indications of the Situated Phenomenon approach. In other words, from reading the transcription of the interviews, establishing, and grouping units of meaning and constructing a nomothetic matrix containing the identification of units of meaning in their convergences and divergences grouped in each thematic category. Three categories emerged from this process: A) The centre of knowledge; B) Colonial violence in all its aspects; C) Confrontations. Based on these categories, the speeches and the dialogue with the theoretical foundations were presented, enabling the understanding of the aspects of the phenomenon studied. The categories revealed a scenario richly marked by the colonialities of power, being and knowledge, in which various mechanisms of maintenance of power structures are present: the racialization and hypersexualization of Brazilian women's bodies, the distancing of women from science in the name of traditionalism/conservatism by patriarchy, the delegitimization of knowledge from the global South and the contradictory appropriation of it in search of prestige, in addition to various types of violence such as racism, xenophobia, sexism and discrimination against queer people. We learned from the participants that in addition to dealing with the “common” aspects of academic life, being a Brazilian female researcher in Portugal is also fighting against stereotypes, linguistic prejudice, epistemicide, transphobia, racism and other forms of violence. This thesis comprises a denunciation text of the condition of Brazilian women scientists in Portugal.